GAYA HIDUP PEREMPUAN DUGEM DI KOTA PEKANBARU - Ulfa Honesty; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Lifestyle of woman dugem in Pekanbaru city. This research was conducted in the city of Pekanbaru more precisely in MP Club. The purpose of this study is to find out how the lifestyle of women who follow the lifestyle of dugem other than that to know and get the overall data about the factors that form a person following the lifestyle dugem. Subjects in this study amounted to 5 people ie women who follow the lifestyle of dugem. The author uses descriptive qualitative methods and the data are analyzed qualitatively and using observational data collection techniques which include documentation and interviews. From the results of research conducted the authors found that lovers dugem identical with the people who hightclass because dugem require a lot of money. To be able to really enjoy the atmosphere of clubbing informants consuming cigarettes, liquor and narcotics. In addition they like to look glamorous and open to look beautiful and sexy. Can be concluded clubbing activity is a lifestyle with a high level of consumptive, just to just get fun for a moment. To realize the lifestyle of dugem in need of some capital, ranging from social capital, economic, cultural and symbolic. If one does not exist then clubbing activities will not go smoothly.Keywords: Lifestyle, Women Dugem, Capital